استخدام طريقة Mind Mapping لترقية قدرة الطلاب على القواعد النحوية - Miswarul Abdi Aziz (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2026)
This research aims to determine the use of the Mind Mapping method to improve students' ability in grammar in the first grade of MAN 3 Pidie. The research method used by the researcher in completing this research is Classroom Action Research (CAR). The data collection methods are observation, questionnaire, test, and documentation. The results of the research show that the application of the Mind Mapping method improves students' ability in grammar in the first grade of MAN 3 Pidie. The researcher conducted grammar teaching steps using the Mind Mapping method, namely the researcher explains the material about grammar using Mind Mapping, then students write it down, and then students identify parts of speech in the first cycle and numbers in the second cycle. Based on the researcher's observation in the first cycle, the average score of the test results was 88.75 and there were 3 students who did not meet the completeness criteria (KKTP), and students were not enthusiastic about learning because they lacked understanding of the material so they did not ask what they did not understand, and this result was incomplete, so the researcher continued to the second cycle and the students' results increased after applying the Mind Mapping method, the average score was 99.85 and all students met the highest completeness criteria (KKTP). The researcher concludes that the teaching activities in the second cycle were successful. This indicates that the application of the Mind Mapping method improves students' ability in grammar.